Ensino de comportamentos básicos de basquetebol para crianças portadoras de síndrome de Down - Stefane, Claudia Aparecida (Universidade Federal de São Carlos, 1996)
The goals of Physical Education have changed in the past few years based on the different interests of the educational institutions and their political orientation, From the beginning of the 70's on. an increasing preoccupation not only with the essays related to Physical Education, but with the graduation of teachers in this area, till then were characterized by the repetition of the motion behavior to be taught. To be able to present a strategy of action different from the perspective discussed above, implies having knowledge of good quality about the leaming process the abilities required for the execution of these contests and more efficient procedures of teaching, for both normal and physical or mental disabled ones. The main aim of this work is to demonstrate that the required behavior background organized as a teaching programme, allow children with Down's Syndrome to leam basic basketball movements in a easy way without the need of motion leaming through repetition. This programme was divided into teaching units, each of them formed by a set of hierarchical abilities in a sequence according to its complexity and functionality. For each motion ability or a set of it, teaching facilities have been elaborated in order to ease the leaming process. An evaluation programme and the performance of each child was done individually, based on the quality of the motion behavior performed, on the frequency of correct abilities presented and on the levei of help offered to the pupils. We have studied four children with Down's Syndrome with age in the six-13 years range, registered in a special educational school in São Carlos city. It was observed that ali individuais, on the whole, showed a performance considered correct in the last sessions, whose objective was the leaming of behaviors considered more complex, faster when compared to the leaming in the beginning of the programme, indicating that the individuais learned how to leam. It also enabled the teacher to quickly and easily identify the abilities involved in the behaviors and the degree of difficulty presented by the students in their acquisition, and thus choose and/or modify the strategies for the teaching of each and every objective. These results may contribute both to the practice of physical education teachers, in the perspective of a transforming action, and to increasing the knowledge on how individuais with Down's Syndrome leam motion behavior and which benefits may be derived from them.
Keywords: Basquetebol; Educação especial; Síndrome de down; Capacidade motora; Programa de ensino; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM